(untitled) (Journal of Naval Architecture and Marine Engineering, 2025)
The current study examines the Williamson fluid flow on a stretching sheet under the effects of MHD and porous material. In addition, the effects of different characteristics—such as heat source, viscous dissipation, joule heating, and chemical reaction—are examined. The influence of solutal stratification factors and temperature was also investigated.. Partial differential equations are used to represent the problem’s governing non-linear equations. These equations are converted into a set of non-linear ordinary differential equations with the necessary similarity transformations. The resulting equations are solved numerically using the Keller Box technique. The influence of various parameters is examined by constructing graphs of velocity, temperature, concentration. Additionally, local parameters are computed and compared with findings from earlier research; the results show compatibility. Profiles of velocity exhibit decreasing behaviour in case of Williamson, Magnetic, and Permeable parameter. Profiles of temperature exhibit increasing behaviour in case of Williamson, Magnetic, Radiation, Joule heating, Heat source, Eckert number parameters whereas opposite trend is witnessed in case of Prandtl number, thermal stratification parameters. Concentration profiles enhances in case of Williamson, Magnetic, permeability parameters and opposite behaviour is examined in case of Chemical reaction, solutal stratification, Schmidt number parameters. Journal of Naval Architecture and Marine Engineering, 22(1), 2025, pp. 49-61